Direct conversion of formaldehyde to ethylene glycol via photocatalytic carbon–carbon coupling over bismuth vanadate. Issue 17 (5th August 2016) - Shen, Zebin; Xie, Shunji; Fan, Wenqing; Zhang, Qinghong; Xie, Zaiku; Yang, Weimin; Wang, Yangdong; Lin, Jinchi; Wu, Xuejiao; Wan, Huilin; Wang, Ye
Abstract : Formaldehyde can be directly converted to ethylene glycol and glycolaldehyde via photocatalytic C–C coupling over BiVO4 under visible light. Abstract : We report a novel and direct conversion of formaldehyde into C2 compounds, in particular ethylene glycol, via photocatalytic carbon–carbon coupling over BiVO4, a visible-light-responsive and robust semiconductor. The generation of V 4+ on BiVO4 surfaces enhanced the photocatalytic formation of C2 compounds.